Pengembangan Panduan Eksperimen Fisika Menggunakan Smarthphone dengan Aplikasi Phyphox Pada Materi Tumbukan - Nurfadilah Nurfadilah; Ishafit Ishafit; R Herawati; E Nurulia (Universitas PGRI Semarang, 2019)
The purpose of this study was to study the validity and response of students towards developing a physics experiment guide using a smartphone with a phyphox application on collision material. This research is a development research (Research and Development) with ADDIE development model consisting of five meetings namely Analysis, Design, Development, Implementation and Evaluation. This study uses descriptive analysis techniques, namely by calculating the percentage value of the results of validation and student responses using a questionnaire instrument. The results of the material expert validation of 85% were very feasible to use and the results of validation by the teacher were 81%, the category was very suitable to use. The results of student questionnaire responses to the experimental technique used phyphox by 90%. Can be used to support physics learning